2018
DOI: 10.1051/matecconf/201823003007
|View full text |Cite
|
Sign up to set email alerts
|

Alkali activated cements mix design for concretes application in high corrosive conditions

Abstract: This paper covers the results of development of corrosion resistant ash alkali-activated cements based on regulation of phase composition of the hydration products through changing the alkali content, content of calciumcontaining cement constituents resulting in the increase strength and density of the cement stone. The results of study suggested to conclude that the cement compositions with predominance in the hydration products of weakly soluble low basic hydrosilicates of calcium, hydrogarnets and minerals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 6 publications
0
23
0
2
Order By: Relevance
“…The alkaline activation of aluminosilicate raw materials is widely used in the production of modern building materials [11]. Concrete based on the alkaline-activated types of cement is characterized by the increased indicators of strength [12], heat resistance [13], corrosion resistance [14], sulfate resistance [15], frost resistance [16], water resistance [17], compared to analogs based on conventional clinker concrete. Along with the high performance properties, the alkaline-activated slag cement can be used as a base of decorative materials [18].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The alkaline activation of aluminosilicate raw materials is widely used in the production of modern building materials [11]. Concrete based on the alkaline-activated types of cement is characterized by the increased indicators of strength [12], heat resistance [13], corrosion resistance [14], sulfate resistance [15], frost resistance [16], water resistance [17], compared to analogs based on conventional clinker concrete. Along with the high performance properties, the alkaline-activated slag cement can be used as a base of decorative materials [18].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Given this, there is a need to develop reliable methods for processing galvanic waste. Known methods of neutralization of hydroxide sludge are associated with their use as additives in the production of various materials: concrete [5], expanded clay [6], asphalt [7], Portland cement [8], bricks and ceramics [9]. It is also possible to produce pigments and catalysts from them [10].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Previous studies have shown that alkaline cements are resistant to the effect of aggressive environment [11], they excellently interact with solutions of sulphates and chlorides [12], and possess a wide range of unique operational properties [13]. They make it possible to reliably fix in their structure the elements of radioactive and HM, not only at the physical [14] but also at the chemical level [15].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%